A Meta‐analytic Integration and Test of Psychological Climate Dimensionality. Issue 3 (1st December 2014) - Benzer, Justin; Horner, Margaret
<x xml:space="preserve">Abstract</x> There is no consensus as to what constructs should be considered to be psychological climate. Further, there is no clear taxonomy of psychological climate, although the climate literature suggests that psychological climate perceptions should form higher‐order (i.e., abstract, broad) dimensions. Two meta‐analyses have been conducted to evaluate higher‐order frameworks, but neither study tested the psychometric structure of their hypothesized models. The current meta‐analysis estimated the intercorrelations and criterion‐related validity of 23 psychological climate constructs in order to test the theoretical frameworks proposed by prior meta‐analyses. Confirmatory factor analyses supplemented by a method analogous to item‐to‐scale correlations indicated little empirical support for the a priori frameworks. Results suggest that that psychological climate may be parsimoniously represented by two dimensions. Task climate was most strongly indicated by supervisor goal setting, innovation, and organizational responsiveness. Relational climate was most strongly indicated by work group warmth and social rewards. A path analysis was estimated to test whether job satisfaction partially mediated the association between psychological climate and the outcomes of job performance, turnover intentions, and psychological well‐being. Results provide guidance to researchers and practitioners interested in measuring perceptions of the work environment. © 2014 Wiley Periodicals, Inc.